Gaya Kepemimpinan dan Disiplin Kerja Terhadap Motivasi Kerja serta Implikasinya Pada Kinerja Karyawan PT. PAN PACIFIC INSURANCE - Cicih Ratnasih; Sastra Ronauli Siahaan (Fakultas Ekonomi Universitas Borobudur, 2021)
The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 94 people. The data processing method uses the path analysismethod with the help of SPSS version 22. Statistical testing uses the individual parametersignificance test (t test) and simultaneous significance test (F test).The results showed that simultaneously the variables, leadership style and work disciplineon work motivation and its implications for employee performance. Partially shows that analysis1: leadership style variables have a significant effect on employee performance, while analysis 2:work discipline variables have a significant effect on employee performance and in analysis 3:work motivation variables have an effect on employee performance. significant to employeeperformance.Keywords: leadership style and work discipline on work motivation and its implications foremployee performance.